2023
DOI: 10.1037/tra0001254
|View full text |Cite
|
Sign up to set email alerts
|

Impact of family rejection and racism on sexual and gender minority stress among LGBTQ young people of color during COVID-19.

Abstract: Objective: Given the inequitable impact of COVID-19 on sexual and gender minority (SGM) youth and current sociopolitical racial justice concerns in the United States, this study examines the impact of SGM-related family rejection and racism since the start of COVID-19 on SGM-related internalized homophobia and identity concealment among SGM college students of color (SOC). Method: Participants were a subset of SOC (n = 200) from a larger nonprobability cross-sectional study about minority stress and COVID-19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 52 publications
(90 reference statements)
1
6
0
Order By: Relevance
“…Studies show parents who knew their children's sexual orientation/behavior were more likely to reject these identities which resulted in the dissolution of their relationships [65]. Prior research has also found that family rejection of identity is detrimental to SMM's mental and physical health [66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show parents who knew their children's sexual orientation/behavior were more likely to reject these identities which resulted in the dissolution of their relationships [65]. Prior research has also found that family rejection of identity is detrimental to SMM's mental and physical health [66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Given the aforementioned pressure parents of LGBTQ+ Asian Americans may feel to ensure children conform to oppressive structures to allow them to live easier lives (Ma & Lan, 2022) combined with colonial impositions of homophobic and transphobic ideologies (Laurent, 2005), we might then see those structural issues manifest in family rejection of their children’s LGBTQ+ identities. Experiencing family rejection has been associated with a plethora of negative mental health outcomes for LGBTQ+ people (Russell, 2019; Ryan et al, 2009; Salerno et al, 2023), which makes sense given the critical role that family connections play developmentally. Family rejection, reflecting a failure to meet familial, cultural, and/or religious expectations (i.e., filial piety), may also lead to LGBTQ+ Asian Americans internalizing feelings of shame (Hu & Wang, 2013; Huang et al, 2016).…”
Section: Lgbtq+ Asian American Familial Experiencesmentioning
confidence: 99%
“…Notably, there is a dearth of studies on the impact of COVID-19 on the mental health of multiply minoritized communities, though a range of related risk factors have been identified for LGBTQ+ individuals of color, including the potential for experiencing multiple sources of discrimination and limited access to affirming care (Pacheco et al, 2021). There is also nascent work with sexual and gender minority individuals of color suggesting that increased racism and family rejection have been associated with greater odds for experiencing internalized homophobia since the start of COVID-19 (Salerno et al, 2022), which may lead to poorer mental health outcomes. Altogether, these experiences may have contributed to a rise in mental health disparities among minoritized individuals, as well as among those with multiply minoritized identities (e.g., individuals who identify as both sexual and racial/ethnic minorities).…”
Section: Impact Of the Covid-19 Pandemic On Minoritized Communitiesmentioning
confidence: 99%